Next generation sequencing uncovers multiple miRNAs associated molecular targets in gallbladder cancer patients - Rahul Saxena; Baskar Chakrapani; M. P. Sarath Krishnan; Amit Gupta; Sweety Gupta; Jayanta Das; Subash C. Gupta; Anissa A. Mirza; Shalinee Rao; Bela Goyal (Scientific Reports)
Abstract Gallbladder cancer (GBC) is a lethal disease with surgical resection as the only curative treatment. However, many patients are ineligible for surgery, and current adjuvant treatments exhibit limited effectiveness. Next-generation sequencing has improved our understanding of molecular pathways in cancer, sparking interest in microRNA-based gene regulation. The aim of the study is to identify dysregulated miRNAs in GBC and investigate their potential as therapeutic tools for effective and targeted treatment strategies. GBC and control tissue samples were sequenced for miRNA expression using the Illumina HiSeq platform. Biological processes and related pathways were determined using the Panther and Gene Ontology databases. 439 significantly differentially expressed miRNAs were identified; 19 of them were upregulated and 29 were downregulated. Key enriched biological processes included immune cell apoptosis, endoplasmic reticulum (ER) overload response, and negative regulation of the androgen receptor (AR) signaling pathway. Panther analysis revealed the insulin-like growth factor (IGF)-mitogen activated protein kinases (MAPK) cascade, p38 MAPK pathway, p53 pathway, and FAS (a subgroup of the tumor necrosis factor receptor) signaling pathway as highly enriched among dysregulated miRNAs. Kirsten rat sarcoma virus (KRAS), AR, and interferon gamma (IFN-γ) pathways were identified among the key pathways potentially amenable to targeted therapy. We concluded that a combination approach involving miRNA-based interventions could enhance therapeutic outcomes. Our research emphasizes the importance of precision medicine, targeting pathways using sense and anti-sense miRNAs as potential therapies in GBC.